Health and politics : appraisal and evaluation of the provision of health and mental health services for Blacks in South Africa - O'Donoghue, Sean B (Rhodes University, Faculty of Humanities, Department of Psychology, 1989)
The aim of this study has been to examine, in the light of recent events in the field of Health Care in South Africa, the remarks and claims made by the World Health Organization, and the American Psychiatric Association between 1976 and 1978 on Health Care services, as provided for Blacks, by the South African government. In two reports, these organizations instituted the earliest, and arguably most significant claims against South Africa's system of Health Care. This study sketches firstly the political genesis and social context of the WHO, and APA examinations. Secondly, this study evaluates responses made by the South African State to the critical climate inspired by the above mentioned reports, through a close analysis of recent events associated with the politics, and provision of Health Care Facilities - particularly with regard to Black South Africans. This analysis suggests that the governments' earlier tentative policy of privatisation (which was soundly condemned by WHO and the APA) has been even more enthusiastically pursued - in contradiction to it's avowed policies of Commu ity Health Care, and to the continuing detriment of those South African communities who are in most need of adequate Health Care services. The study concludes that the criticisms raised by the WHO and APA had the effect of inspiring positive reforms in South Africa's health services, but in no way thwarted the governments', at first only tentative plans, to increasingly privatise it's psychiatric and other medical institutions.
Keywords: Black people -- Mental health -- South Africa; Mental health services -- South Africa